Opportunity Cost Classification of Goods and Markets - Davor Mance; Nenad Vretenar; Jana Katunar (Central European Public Administration Review)
Sixty years ago, Samuelson’s “Pure Theory of Public Expenditure” expounded the classification of goods, and Bain’s “Economies of Scale, Concentration and the Condition of Entry in Twenty Manufacturing Industries” expounded the structure-conduct-performance paradigm. To the present day, rivalry in- and excludability from consumption classify goods, and subadditivity and irreversibility in production classify market structure. Opportunity costs of production in the form of prospective sunk costs incentivise investment and production, and the sunk costs themselves induce subadditivities, specialization and convexity of the marginal rate of technical substitution. Opportunity costs in consumption are determined by the marginal costs of replacement. In light of the recent Nobel price award to Jean Tirole, we revisit some of the forgotten discussions and clarify some of the terminology under a more economic framework of opportunity costs.